Examining the Mediating Role of Competitive Priorities (CP) for the Relationship Between Competitive Challenges (CC) and Competitive Superiority (CS) in The Banking System (BS) at Dongola Locality (DL) in The Northern State in Sudan - Houssin, Oussam Mouaouia; Mahmoud Hachem, Abdelhamid (Finance and Business Economies Review, 2020)
The study aimed to examining the mediating role of (CP) for the relationship between (CC) and (CS) in the (BS) at (DL). The problem of study is that many branches banks in (DL) still do not realize the importance role of (CP) in facing (CC) and its effect on (CS). The study found (CP) mediating the relationship between (CC) and (CS) in (BS) at (DL) with an Indirect Effect of (0.661). The study recommended activate some practicing that enable to achieving (CS) in branches banks under study.